ANALISIS STRATEGI PEMASARAN BERBASIS AI (ARTIFICIAL INTELLIGENCE), UNTUK MENINGKATKAN EFEKTIVITAS KAMPANYE, MELALUI OPTIMALISASI ENGAGEMENT KONSUMEN UKM JABODETABEK DI SOSIAL MEDIA - Erry Priyambodo; Lussia Mariesti Andriany; Fathorrahman Fathorrahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The development of digital technology in the era of the industrial revolution 4.0 has brought significant changes to various aspects of business, including marketing strategies. Currently, social media has become a primary marketing channel for Small and Medium Enterprises (SMEs) because it can reach consumers widely, quickly, and at a relatively low cost. The purpose of this study is to analyze consumer engagement to mediate the relationship between AI-based marketing strategies and the effectiveness of SME digital campaigns on social media. The sampling technique used purposive side. Method The research used quantitative methods with survey research types. The research population was all SMEs that use social media as a means of digital-based promotion and marketing in the Greater Jakarta area (Jakarta, Bogor, Depok, Tangerang, Bekasi) with a sample of 100 people. The results of the study are 1) AI-based marketing strategies have a positive and significant influence on SME consumer engagement on social media, 2) AI-based marketing strategies have a positive and significant influence on the effectiveness of SME digital campaigns on social media, 3) Consumer engagement has a positive and significant influence on the effectiveness of SME digital campaigns on social media and, 4) Consumer engagement is proven to be a mediating variable between AI-based marketing strategies and the effectiveness of SME digital campaigns on social media.